35. CURRENT SITUATION AND SOME FACTORS RELATED TO ENVIRONMENTAL SANITATION BEHAVIOR OF DAO PEOPLE IN KIM BOI DISTRICT, HOA BINH PROVINCE IN 2021 (Vietnam Journal of Community Medicine, 2024)
Background: To help managers have a basis to improve environmental sanitation conditions forethnic people in general and the Dao ethnic group in particular.Objective: Describe the current situation and some factors related to the management and protectionof the ecological environment of the Dao people in Kim Boi District, Hoa Binh Province in 2021.Research subjects and methods: Cross-sectional descriptive research, quantitative combined withqualitative research conducted on 603 Dao households living in the Kim Boi district from January2021 to October 2021.Results and conclusions: The proportion of Dao people who have satisfactory behavior onenvironmental sanitation, but is low, is as follows: 39.6% have satisfactory behavior on usinghygienic water sources; 24.7% of behaviors achieved human excrement management; 14.1% onquality classification; 26.6% on waste treatment. Some factors related to environmental sanitationbehavior are Household economy, physical hygiene, education level, and knowledge and attitudes ofthe Dao people about sanitation. Building a communication model to change environmentalsanitation actions for Dao people in Hung Son commune.
Keywords: Current situation, related factors, environmental sanitation, Dao people, Kim Boi District.